A cross-cohort comparison of the prevalence and clinical significance of Alzheimer’s disease biomarkers in people with versus without HIV - Lillian Ham; Olivia Villers; Judith D. Lobo; Tyler R. Bell; Debralee Cookson; Douglas Galasko; Scott L. Letendre; Mark W. Bondi; David J. Moore; Erin E. Sundermann (Journal of NeuroVirology, 2026)
With over half of people with HIV (PWH) in the U.S. entering older adulthood, identifying markers to distinguish Alzheimer’s disease (AD) and its precursor, amnestic mild cognitive impairment (aMCI), from other forms of neurocognitive impairment among PWH is urgent. We examined how HIV and aMCI status relate to AD CSF biomarkers in adult PWH and people without HIV (PWoH) characterized for aMCI. We included 80 PWH from the National NeuroHIV Tissue Consortium and 80 PWoH from the Wisconsin Registry for Alzheimer’s Prevention. Binary logistic regressions of AD-related CSF biomarker positivity (Aβ 42, Aβ 42 /Aβ 40, t-tau, p-tau 181 , Aβ 42 /t-tau) were conducted with HIV serostatus, aMCI status, HIV x aMCI interaction, and demographic covariates. Among PWH, we examined how HIV-disease characteristics relate to AD biomarker positivity. No HIV x aMCI interactions were detected. Regardless of aMCI status, having HIV was associated with higher odds of CSF Aβ 42 (OR = 7.97) and Aβ 42 /Aβ 40 (OR = 6.06) positivity, suggesting increased cerebral Aβ plaque burden. Regardless of HIV serostatus, having aMCI was associated with higher odds of CSF p-tau 181 positivity (OR = 3.64). Neither HIV nor aMCI status related to Aβ 42 /t-tau positivity. No HIV-disease characteristics related to AD biomarker positivity. Higher CSF Aβ positivity in PWH versus PWoH, regardless of aMCI status, suggests that HIV disease promotes amyloidosis; however, whether positive CSF biomarkers in PWH raises risk for future cognitive impairment and AD remains to be explored longitudinally. Like PWoH, elevated CSF p-tau 181 among PWH may indicate increased risk for AD-related memory impairment.